2015
DOI: 10.1186/s12934-015-0276-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RCK2 MAPKAP (MAPK-activated protein kinase) rescues yeast cells sensitivity to osmotic stress

Abstract: BackgroundSaccharomyces cerevisiae is the micro-organism of choice for the conversion of fermentable sugars during beverage or bioethanol fermentations. These fermentations are characterised by high osmotic stress on a yeast cell, with selected brewing fermentations beginning at 20–25% fermentable sugars and bioethanol fermentations at 13% fermentable sugars.ResultsRCK2 encodes for a MAPKAP (MAPK-activated protein kinase) enzyme and was identified on a locus by QTL analysis in yeast cells under osmotic stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Results here revealed that use of tetracycline-regulated system in a fermentation correlated expression of a desired gene with a phenotype; this work follows up a similar study from our previous research group [ 31 ]. Cytochrome C oxidase activity under acetic acid stress has been highlighted previously as pre-cursors for programmed cell death in yeast; however expression of COX20 correlating with acetic acid or oxidative tolerance has not been shown previously.…”
Section: Discussionsupporting
confidence: 84%
“…Results here revealed that use of tetracycline-regulated system in a fermentation correlated expression of a desired gene with a phenotype; this work follows up a similar study from our previous research group [ 31 ]. Cytochrome C oxidase activity under acetic acid stress has been highlighted previously as pre-cursors for programmed cell death in yeast; however expression of COX20 correlating with acetic acid or oxidative tolerance has not been shown previously.…”
Section: Discussionsupporting
confidence: 84%
“…Likewise, yeast eEF2 is phosphorylated by the kinase Rck2 during osmotic stress (Teige, Scheikl, Reiser, Ruis, & Ammerer, 2001). Rck2 is essential for tolerance to osmotic stress, underlining the importance of elongation regulation under these conditions (Kumar, Hart, Wimalasena, Tucker, & Greetham, 2015). Furthermore, the master regulator Hog1, which activates Rck2, is also activated by independent mechanisms during both endoplasmic reticulum (ER) stress (Bicknell, Tourtellotte, & Niwa, 2010) and oxidative stress (Lee et al, 2017), implicating elongation control by eEF2 phosphorylation under these conditions.…”
Section: Elongationmentioning
confidence: 99%
“…Another report has been obtained for radiation-induced chromosome damage by ethyl acetate fraction of A. rohituka [13]. A bioactive compound rohitukine extracted from A. rohituka possesses immune-modulatory, anti-inflammatory and anti-cancer properties, and also serves as a precursor for the synthesis of P-276-00 (Piramal Healthcare Limited, Mumbai, India) and flavopiridol, an anticancer drug [14,15]. The first study for isolation of rohitukine and its analog, rohitukine N-oxide has been demonstrated in endophytic fungi Gibberella fujikuroi MTCC 11382 obtained from A. rohituka [16].…”
Section: Introductionmentioning
confidence: 99%